Comparative Study of Organic and Conventionally Produced Tomatoes of the selected area of Dhankuta, Nepal - Yadav, Chandradip Kumar; Bhattarai, Ajaya (Journal of Nepal Chemical Society, 2018)
Available with Fulltext.